2021
DOI: 10.15184/aqy.2021.8
|View full text |Cite
|
Sign up to set email alerts
|

Emblems and spaces of power during the Argaric Bronze Age at La Almoloya, Murcia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
0
18
0
6
Order By: Relevance
“…Nevertheless, the radiocarbon date obtained for the burial of the hypogeum 8 is very close to the oldest dates for El Argar contexts with silver artefacts (it is not statistically different from one of the two oldest dates: 3635 ± 60 BP and 3670 ± 70 BP, according to Montero Ruiz (1999: 352). On the other hand, the expertise of the silversmith that made the pommel of the dagger is comparable to whom produced the silver items recorded in the Argaric grave 38 of La Almoloya (Murcia) (Lull et al 2021) with parallels in the grave goods of the Argaric cist of Los Villares (Andújar, Jaén), namely the silver cover of the handle of a copper awl or the silver cover of the rim of a carinated ceramic vessel (Carrasco et al 1979). However, it should be noted that the grave goods from HP5 are more than a hundred years older than those recorded in grave 38 of La Almoyola, which raises questions, namely where did silver metallurgy first appear in the Iberian peninsula and in which direction the spread of this metallurgy occurred.…”
Section: Middle Southwestern Bronze Age Early Archaeological Contexts -Parallels Prestige Symbols and Social Stratificationmentioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, the radiocarbon date obtained for the burial of the hypogeum 8 is very close to the oldest dates for El Argar contexts with silver artefacts (it is not statistically different from one of the two oldest dates: 3635 ± 60 BP and 3670 ± 70 BP, according to Montero Ruiz (1999: 352). On the other hand, the expertise of the silversmith that made the pommel of the dagger is comparable to whom produced the silver items recorded in the Argaric grave 38 of La Almoloya (Murcia) (Lull et al 2021) with parallels in the grave goods of the Argaric cist of Los Villares (Andújar, Jaén), namely the silver cover of the handle of a copper awl or the silver cover of the rim of a carinated ceramic vessel (Carrasco et al 1979). However, it should be noted that the grave goods from HP5 are more than a hundred years older than those recorded in grave 38 of La Almoyola, which raises questions, namely where did silver metallurgy first appear in the Iberian peninsula and in which direction the spread of this metallurgy occurred.…”
Section: Middle Southwestern Bronze Age Early Archaeological Contexts -Parallels Prestige Symbols and Social Stratificationmentioning
confidence: 82%
“…However, it should be noted that the grave goods from HP5 are more than a hundred years older than those recorded in grave 38 of La Almoyola, which raises questions, namely where did silver metallurgy first appear in the Iberian peninsula and in which direction the spread of this metallurgy occurred. The different alloys of HP5 dagger endorse its extraordinary value as a symbol of high status or an emblem (following Lull et al 2021) among those communities of the beginning of the 2 nd millennium BC.…”
Section: Middle Southwestern Bronze Age Early Archaeological Contexts -Parallels Prestige Symbols and Social Stratificationmentioning
confidence: 99%
“…One might wonder why the presence of powerful women in the past is newsworthy, but such androcentric extensions of today's world into the past persist (Conkey & Spector, 1984; Geller, 2017, 2019). The 21st century has witnessed notable revisions of received wisdom concerning powerful women in the past, frequently revealed in bioarchaeological studies (Buikstra et al, 2004; Knüsel, 2002; Lull et al, 2021; Price et al, 2019)…”
Section: Inferring Ancient Identitiesmentioning
confidence: 99%
“…The 21st century has witnessed notable revisions of received wisdom concerning powerful women in the past, frequently revealed in bioarchaeological studies (Buikstra et al, 2004;Knüsel, 2002;Lull et al, 2021;Price et al, 2019) There are, thus, many reasons to extend the study of biological sex into the more challenging domain of gender (Ghisleni et al, 2016;Gilchrist, 2004;Sofaer, 2012;Walker & Cook, 1998). Among the most central is enriching appreciation of variability in past lives, (e.g., Bolger & Wright, 2012, Tung, 2021Section 7); examples of gender flexibility counter the heteronormative, essentialized vision of the past that all too often informs visions of binary sex categorization today (Geller, 2017(Geller, , 2019).…”
Section: Skeletal Sex To Gendermentioning
confidence: 99%
“…It is worth noting that the status of women during the Bronze Age may have been different between China and Europe. For example, archaeological working in southeastern Spain revealed that women could have been correlated to the ruling class in the Bronze Age El Argar society (about 4,000 years ago) (Lull et al 2021), which would denote a totally different patterns of labor division.…”
Section: Spinal Osteophytosis and Gender-based Labor Divisionsmentioning
confidence: 99%